Lifestyle Characteristics and Dietary Habits in Romanian Patients with Periodontitis: A Cross-Sectional Study - Ana Maria Hofer; Andrei Picos; Bogdana Adriana Nasui; Alexandra Dădârlat-Pop; Monica Popa (Healthcare, 2026)
Background/Objectives: Periodontitis is a multifactorial chronic inflammatory disease influenced by behavioral, metabolic, and lifestyle-related factors. This study aimed to examine the associations of selected dietary habits, body mass index (BMI), physical activity, smoking, and oral hygiene behaviors with clinical periodontal parameters in a clinical sample of adults with periodontitis from northwestern Romania. Methods: This cross-sectional study included 204 adults with clinically diagnosed periodontitis. Sociodemographic characteristics, smoking status, physical activity, toothbrushing frequency, tooth mobility, and selected dietary habits were assessed using a structured questionnaire. Periodontal status was clinically evaluated using periodontal probing depth (PPD), clinical attachment loss (CAL), and bleeding on probing (BOP), while BMI was calculated from anthropometric measurements. Descriptive and inferential statistical analyses were performed to evaluate associations between the investigated factors and periodontal parameters. Multivariable linear regression models were constructed separately for PPD, CAL, and BOP, simultaneously including age, sex, BMI, smoking status, physical activity frequency, toothbrushing frequency, tooth mobility, education level, and the assessed dietary habits. Results: In the fully adjusted multivariable analyses, fish consumption 1–3 times/week was independently associated with lower PPD, whereas sweets consumption 1–3 times/week was independently associated with higher PPD. Carbonated beverage and sweets consumption 1–3 times/week were independently associated with higher BOP. Although the multivariable model for CAL was statistically significant overall, none of the individual predictors included in the model reached statistical significance. BMI and physical activity frequency were not independently associated with PPD, CAL, or BOP after simultaneous adjustment for the other variables. Age group was significantly associated with CAL category (χ2(2) = 13.28, p = 0.001, Cramér’s V = 0.255), while educational level was significantly associated with toothbrushing frequency (χ2 = 62.26, p < 0.001, Cramér’s V = 0.39). Conclusions: Selected dietary habits were independently associated with PPD and BOP after adjustment for demographic, anthropometric, lifestyle, and oral hygiene factors, whereas no individual predictor was independently associated with CAL in the fully adjusted model. BMI and physical activity were not independently associated with the periodontal parameters examined. These findings emphasize the multifactorial nature of periodontal status and suggest that specific dietary habits may be associated with different clinical dimensions of periodontal disease. However, causal relationships cannot be established due to the cross-sectional design of the study. Prospective studies using validated dietary assessment methods are needed to confirm these associations.